2013
DOI: 10.1146/annurev-publhealth-031912-114353
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Economics of Health and Health Care

Abstract: People often make decisions in health care that are not in their best interest, ranging from failing to enroll in health insurance to which they are entitled, to engaging in extremely harmful behaviors. Traditional economic theory provides a limited tool kit for improving behavior because it assumes that people make decisions in a rational way, have the mental capacity to deal with huge amounts of information and choice, and have tastes endemic to them and not open to manipulation. Melding economics with psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(186 citation statements)
references
References 30 publications
3
170
0
2
Order By: Relevance
“…These shortcuts are usually effective (42) but can sometimes lead people astray, resulting in damaging cognitive biases or systematic departures from predictable rational economic behavior ( Table 1). Because incentive schemes rely on providers responding in predictable and rational ways, understanding cognitive biases offers both an explanation for the failings of previous incentive schemes and a potential framework for designing more effective schemes in the future (75).…”
Section: Insights On Physician Response To Incentives From Social Psymentioning
confidence: 99%
“…These shortcuts are usually effective (42) but can sometimes lead people astray, resulting in damaging cognitive biases or systematic departures from predictable rational economic behavior ( Table 1). Because incentive schemes rely on providers responding in predictable and rational ways, understanding cognitive biases offers both an explanation for the failings of previous incentive schemes and a potential framework for designing more effective schemes in the future (75).…”
Section: Insights On Physician Response To Incentives From Social Psymentioning
confidence: 99%
“…Recent work in behavioral economics has shown that shopping for health insurance is an unpleasant task, with imperfect information, and many people avoid it if possible, even if they are in a plan that does not meet their needs or a more affordable option is available. 29 Noted health economist Uwe Reinhardt has compared using the US health care system to walking into a department store blindfolded and months later being handed a statement that says, "Pay this amount." 30 The titles of popular press articles indicate some of the issues: "Revealing a Health Care Secret: The Price" and "Shopping for Health Care, A Fledgling Craft, " for example.…”
Section: Shopping Blindfolded: Choice and Costsmentioning
confidence: 99%
“…The framework integrates concepts from Behavioural Economics (Rice 2013), the foundation for the default-based (opt-out) study intervention; the Health Belief Model, to explore possible relationships between the participants' beliefs about HIV and their testing practices (Rosenstock 1974); and Normalisation Process Theory, a guide for implementation of opt-out HIV testing at the operational level (May 2013).…”
Section: Introductionmentioning
confidence: 99%